Local Destruction of Tumors and Systemic Immune Effects - Tranberg, Karl-Göran (Frontiers in Oncology, 2021)
Current immune-based therapies signify a major advancement in cancer therapy; yet, they are not effective in the majority of patients. Physically based local destruction techniques have been shown to induce immunologic effects and are increasingly used in order to improve the outcome of immunotherapies. The various local destruction methods have different modes of action and there is considerable variation between the different techniques with respect to the ability and frequency to create a systemic anti-tumor immunologic effect. Since the abscopal effect is considered to be the best indicator of a relevant immunologic effect, the present review focused on the tissue changes associated with this effect in order to find determinants for a strong immunologic response, both when local destruction is used alone and combined with immunotherapy. In addition to the T cell-inflammation that was induced by all methods, the analysis indicated that it was important for an optimal outcome that the released antigens were not destroyed, tumor cell death was necrotic and tumor tissue perfusion was at least partially preserved allowing for antigen presentation, immune cell trafficking and reduction of hypoxia. Local treatment with controlled low level hyperthermia met these requisites and was especially prone to result in abscopal immune activity on its own.